THE IMPROVEMENT OF MISPRONUNCIATION ENCOUNTERED BY MOST YOUNG ENGLISH LEARNERS - Dianatalia Agustine; Indah Arvianti; Eko Heriyanto (Universitas Aki, 2022)
Mispronunciation is a critical issue encountered by most young English learners in a second language learning that causes low spoken English proficiency, which plays important roles today. The objectives of this study were to identify the segmental changes resulted in the articulation of English mispronounced words produced by most young learners, to describe the different elements between Indonesian and English sound systems, and to explain the phonological interference of mother tongue in English mispronunciation. This study uses descriptive qualitative research design performed on ten primary school students selected by using purposive sampling in Semarang. Data were collected by using simak method and analyzed by using padan fonetik artikulatoris method. The data suggest that the majority of the participants had difficulty in articulating the words with absent phonemic segments /ɪ, æ, əː, ɔ, ʌ, eɪ, ʊə, ɪə, aɪə, ʃ, θ, ð, ʒ, voiced v/, silent letters <b, d, e, t, w, gh, and r in some cases>, spelling patterns <th, ow, ph, ie, ueue, ough>, and tricky words including several English borrowings that have inconsistent spelling pronunciation. The results showed that the interference of L1 sounds and pronunciation rules occurred through substitution of closest native sounds for absent phonemes, insertion of native sounds, and negative transfer of L1 spelling pronunciation. It can be concluded that most of the young learners mispronounced on words with absent phonemic segments, silent letters, spelling patterns of many letters combination, and several English borrowings.